MANAGERIAL CLUSTERS MODEL IN THE URBAN SOLID WASTE MANAGEMENT - Chung P., Alfonso (2004)
This article deals about the necessary requirements for assessing the application of a Managerial Clusters Model at its starting stage of Urban Solid Waste Segregation, in order to lead it towards recycling, taking into consideration the main variables and proposing a model for supporting its application.